Quantitative Evaluation of the Thermal Heterogeneity on the Surface of Cryotherapy Cooling Pads - Khoshnevis, Sepideh (J Biomech Eng, 2014)
We have investigated thermal operating characteristics of 13 commercially available cryotherapy units (CTUs) and their associated cooling pads using IR imaging. Quantitative examination of the temperature profiles from pad IR images shows diverse, nonuniform temperature distribution patterns. The extent of heterogeneity of the temperature fields was quantified via standard image analysis methods, including thresholding, spatial gradient diagrams, and frequency histogram distributions. A primary conclusion of this study is that it is a misnomer to characterize the thermal performance of a CTU and cooling pad combination in terms of a single therapeutic temperature.